2023
DOI: 10.3390/jcm12216896
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Potentially Fatal COVID-19 Disease in Pregnant Patients Using the Neutrophil-to-Lymphocyte Ratio (NLR)

Dorina Supák,
Balázs Mészáros,
Balázs Turi
et al.

Abstract: Objective: To evaluate the neutrophil-to-lymphocyte ratio (NLR) values’ possible predictive role in fatal and severe cases of COVID-19 disease in pregnant women. Design and data collection: A case-control study was conducted with the inclusion of 45 pregnant COVID-19 patients. All the data were obtained from the hospital information system of Semmelweis University by two of the authors. Results: Statistical analyses showed that NLR values were significantly higher in patients with fatal COVID-19 compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Our research group additionally conducted a case–control study, which included 45 pregnant patients with COVID-19. Statistical analyses revealed that NLR values were notably elevated in patients who succumbed to fatal COVID-19 compared to those who survived the disease ( 78 ).…”
Section: Commentmentioning
confidence: 99%
“…Our research group additionally conducted a case–control study, which included 45 pregnant patients with COVID-19. Statistical analyses revealed that NLR values were notably elevated in patients who succumbed to fatal COVID-19 compared to those who survived the disease ( 78 ).…”
Section: Commentmentioning
confidence: 99%
“…In the second year of the study, besides monitoring the stability of the results previously achieved, we managed to pool all 98 patients' data thus enabling a thorough and updated analysis of whole study protocol parameters. Specifically, comprehensive data compilation on NLR could be undertaken, given that elevated values are indicative of unfavorable outcomes in various contexts, including chronic inflammatory conditions, acute infectious diseases, monitoring severity in SARS-COVID-19, and assessing injury induced by environmentally retrievable toxins [13][14][15][16][17][18][19].Given the promising first-year beneficial effect of FPP supplementation in a number of crucial redox parameters and apoptosis regulation, the present study intended to confirm the stability of that data along a further year of observation to study the profile of NLR and its possible relationships with the other variables.…”
Section: Introductionmentioning
confidence: 99%